2020
DOI: 10.1108/imefm-01-2020-0027
|View full text |Cite
|
Sign up to set email alerts
|

Do ‘Shariah’ indices surpass conventional indices? A study on Dhaka Stock Exchange

Abstract: Purpose This paper aims to examine whether the Sharīʿah indices outperform the conventional indices as evident from Dhaka Stock Exchange (DSE). To achieve the objective, the study, first, assesses the risk adjusted returns of the Sharīʿah and conventional indices and compares the same between the two indices. Second, it examines the short-run and long-run associations between the two indices. Design/methodology/approach The DSEX Sharīʿah index and DSE broad index of the DSE are used as representatives of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Thus, financial performance of Islamic stocks and conventional stocks are similar according to the Treynor ratio. These results are aligned with the findings of Abbes (2012), Jawadi et al (2014), Bayram and Othman (2019), Trabelsi et al (2020) and Aarif et al (2021).…”
Section: Empirical Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, financial performance of Islamic stocks and conventional stocks are similar according to the Treynor ratio. These results are aligned with the findings of Abbes (2012), Jawadi et al (2014), Bayram and Othman (2019), Trabelsi et al (2020) and Aarif et al (2021).…”
Section: Empirical Findingssupporting
confidence: 91%
“…Similarly, while comparing the performance of KATILIM 50 and BIST 100 indexes in Turkey's stock market, Bayram and Othman (2019) find no significant difference between the performance of the KATILIM 50 index and BIST 100 index. The findings of Abbes (2012), Trabelsi et al (2020) and Aarif et al (2021) support the previous studies that there is no substantial difference in return performance between Islamic and conventional stocks in developed and emerging stock markets. In another study, Hussein and Omran (2005) find that DJIM outperforms its counterpart indexes over the bull period and underperforms its counterpart indexes over the bear period.…”
Section: Literature Reviewsupporting
confidence: 81%
“…The extant literature on Islamic finance is extensive. A considerable volume of studies investigated the performance of Islamic finance, particularly Islamic stocks, compared to their conventional peers (e.g., Al-Khazali et al, 2014 ; Dewandaru et al, 2014 ; Ho et al, 2014 ; Akhtar and Jahromi, 2017 ; Hassan et al, 2020 ; Alam and Ansari, 2020 ; Aarif et al, 2020 ; Hasan et al, 2021b ). The comparative performance is measured from diverse perspectives: i.e., risk-adjusted performance, cointegration, and volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides studies on traditional mutual funds (e.g., Bertin and Prather 2009;Chou et al 2016), several studies have been published on investment performance of Islamic equity funds and unit trusts in Malaysia and other Islamic nations (Nassir et al 1997;Ismail and Shakrani 2003;Hassan 2005, 2007;Hayat 2006;Ahmed 2007;Abdullah et al 2007;Taib and Isa 2007;Abderrezak 2008;Dewi and Ferdian 2012;Abdullah and Abdullah 2015;Mansor and Bhatti 2011;Mansor et al 2015;Boo et al 2017;Hammami and Oueslati 2017;Makni et al 2016). Worth exploring are the following studies: a Saudi capital market report on the comparison between Islamic and conventional systems was done by Al Rahahleh and Bhatti (2017), a literature review article by Al Rahahleh et al (2019), and recent articles by Aarif et al (2020) and Azmi et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several analyses (Ahmed 2007;Hayat and Kraeussl 2011;Mansor and Bhatti 2011;Mansor et al 2015) considered fund managers' market timing skill by utilizing the simple market timing model of Treynor and Mazuy (1966), and one study (Low 2012) employed the less sophisticated timing model of Henriksson and Merton (1981). Recently, Rahman et al (2017), (Aarif et al 2020 andAzmi et al (2020) compared the investment performance of ethical equity mutual funds and their traditional counterparts in the US, finding that the former perform no worse than the latter, and there is some evidence of superior security selection and/or market timing skills only among a few of them. Meanwhile, Cujean (2016) found that social interactions among fund managers lead to significant high performance.…”
Section: Introductionmentioning
confidence: 99%